Research literature-seeking behaviours of female lecturers in faculties of education at a Nigerian Federal University - Valentine Joseph Owan; Isu Bassey Ekpe; Imelda Barong Edam-Agbor; Peter Owogoga Aduma; Mercy Valentine Owan (Eureka: Journal of Educational Research, 2025)
Although literature reviews are central to academic writing and teaching, little attention has been paid to how demographic factors such as age, academic rank, and marital status influence literature-seeking behaviours. This study addressed this gap by investigating the literature-seeking behaviours among female lecturers in the Faculties of Education at a Nigerian Federal University. The study involved 148 randomly selected female lecturers. A well-validated survey instrument was used to measure literature-seeking behaviours. The results indicated that the overall extent of literature-seeking habits was not significantly high. Significant age differences were observed in female lecturers’ literature review habits, with younger lecturers exhibiting more favourable behaviours. Additionally, differences in academic rank revealed that assistant lecturers demonstrated the most literature-seeking habits. Furthermore, single female lecturers reported significantly better literature-seeking habits than their married counterparts did. The findings suggest a need for targeted support to enhance literature-seeking behaviours, particularly among older and married lecturers. Mentorship programmes and workshops are needed to promote academic engagement. Future research should explore the reasons for these differences and investigate interventions to improve literature-seeking behaviours across demographic groups.